A 3-stage treatment system for domestic wastewater: Part II. Performance evaluation - Oon, Yin Wee; Law, Puong Ling; Ting, Sim Nee; Tang, Fu Ee (Department of Civil Engineering, Faculty of Engineering, Universiti Malaysia Sarawak, 2013)
A 3-stage micro-scale wastewater treatment system that consisted of 1) a spiral-framed human hair-based filter, 2) a plastic medium mixed flow biotower, and 3) a free surface water wetland system filled with Pistia Stratiotes (water lettuce) operating in series was recently developed and performance tests were conducted. Performance tests were carried out to determine the efficiencies of the system for removal of physically emulsified and free oils, organic matters such as biochemical oxygen demand, ammoniacal-nitrogen, suspended solids, and nutrients such as nitrogen, phosphorus and potassium from semi-synthetic wastewaters. From this study, it was found that the human hair-based filter could retain approximately 73.5% of physically emulsified oils, while the mixed flow biotower was capable of reducing approximately 35.0% biochemical oxygen demand, 57.4% ammoniacal-nitrogen, 51.8% nitrogen, 13.4% phosphorus, 21.8% potassium, and 21.9% reduction in turbidity. The Pistia Stratiotes-based free surface water wetland was found to remove approximately 24.1% biochemical oxygen demand, 30.6% ammoniacal-nitrogen, 38/0% nitrogen, 41.5% phosphorus, 46.7% potassium and 31.7% reduction in turbidity. When the mixed flow biotower and free surface water wetland system were to operate in series, the combined removal efficiencies were approximately 59.2% for biochemical oxygen demand, 87.9% for ammoniacal-nitrogen, 90.6% for nitrogen, 54.9% for phosphorus, 68.5% for potassium, and 59.0% reduction in turbidity. Experimental data also showed that daily uptake rates (mg/kg-day) of organics and nutrients by per kilogram of Pistia Stratiotes were approximately 1,731 mg for biochemical oxygen demand, 1,015 mg for ammoniacal-nitrogen, 1,206 mg for nitrogen, 1,468 mg for phosphorus, and 5,431 mg for potassium.